2015
DOI: 10.1039/c5ra16379j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bond assisted, aggregation-induced emission of digitonin

Abstract: Weakly luminescent glycoside digitonin luminesces strongly after treatment with strong base. This is attributed to the hydrogen bonding interaction between deprotonated digitonin molecules, which lead to restricted rotation around the single bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…On the other hand, non-conjugated so materials that might have a better solubility, lower cost, higher exibility, lower cytotoxicity, better biocompatibility, and naturally occurring, 8 are usually taken for granted as nonemissive materials. Until recently, some non-conjugated materials, such as 1,1,2,2-tetraphenylethane, 9 poly[(maleic anhydride)-alt-(vinyl acetate)], 10 polyisobutene succinic anhydrides and imides, 11 and steroidal saponin digitonin, 12 were reported to show amazing ultraviolet (UV) or blue aggregation-induced emission (AIE). 9,13 Our research work continuously focus on the synthesis, optical properties, and sensing applications of N,N 0 -bis(salicylidene)ethylenediamine (salen), a particular class of salicylaldehyde-based bis-Schiff base (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, non-conjugated so materials that might have a better solubility, lower cost, higher exibility, lower cytotoxicity, better biocompatibility, and naturally occurring, 8 are usually taken for granted as nonemissive materials. Until recently, some non-conjugated materials, such as 1,1,2,2-tetraphenylethane, 9 poly[(maleic anhydride)-alt-(vinyl acetate)], 10 polyisobutene succinic anhydrides and imides, 11 and steroidal saponin digitonin, 12 were reported to show amazing ultraviolet (UV) or blue aggregation-induced emission (AIE). 9,13 Our research work continuously focus on the synthesis, optical properties, and sensing applications of N,N 0 -bis(salicylidene)ethylenediamine (salen), a particular class of salicylaldehyde-based bis-Schiff base (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The diluted aqueous solution of GQD and AuQC@GQD are brownish yellow under daylight, upon irradiation at 365 nm light, the aqueous solution of GQD exhibits blue‐green emission and interestingly the AuQC@GQD exhibits the reddish violet emission (inset of Figure B). The Quantum yield of AuQC@GQD and GQD were found to be 5.53% and 6% (with excitation at 380 nm, Table S1, SI), which was calculated using quinine sulfate as standard . The time‐resolved fluorescence study of GQD and AuQC@GQD are shown in Figure A, Figure S3, SI and Table S2, SI.…”
Section: Resultsmentioning
confidence: 92%
“…The Quantum yield of AuQC@GQD and GQD were found to be 5.53% and 6% (with excitation at 380 nm, Table S1, SI), which was calculated using quinine sulfate as standard. [21] The time-resolved fluorescence study of GQD and AuQC@GQD are shown in Figure 3A, Figure S3, SI and Table S2, SI. The AuQC@GQD exhibited average lifetimes of 2.02 ns (λ ex -344 nm and λ max -450 nm) and 1.39 ns (with respect to λ max -680 nm).…”
Section: Synthesis and Characterizations Of Auqc@gqdmentioning
confidence: 99%
“…Remarkably,w eobserved the gradualb roadening of both these peaks, upon increasing the temperature from 25 to 80 8C( Figure S15, Supporting Information). [40] Hence, we perturbed intramolecular Hbondingb yi ncreasingt he pH of the mediumf rom 7.4 to 8.5. [39] To further validate our hypothesis, we performed temperature-dependent fluorescence spectroscopy on compound 4a in water.I tw as observedt hat, with graduali ncrease in temperature from 25 to 80 8C, the intensity of fluorescence emission was gradually decreased by 3.5 times (Figure 3c), due to the destruction of H-bonding in structure 4a'.I nterestingly, this fluorescence quenching phenomenaw as found to be reversible.…”
mentioning
confidence: 99%
“…Inter-and intramolecular H-bonding leadingt o AIE property is highly sensitivet ot he pH of the medium. [40] Hence, we perturbed intramolecular Hbondingb yi ncreasingt he pH of the mediumf rom 7.4 to 8.5. Interestingly,i tw as observed that compound 4a lost its fluorescencep roperty completely (Figure 3d)l eading to the destruction of H-bonding in structure 4a".A lternatively,d ecreasing the pH from 8.5 to 7.4 resumed the fluorescencep roperty into compound 4a which even retaineda tm uch lower pH 4 ( Figure 3d,e).…”
mentioning
confidence: 99%